2014
DOI: 10.1890/13-1569.1
|View full text |Cite
|
Sign up to set email alerts
|

Complementarity and redundancy of interactions enhance attack rates and spatial stability in host–parasitoid food webs

Abstract: Complementary resource use and redundancy of species that fulfill the same ecological role are two mechanisms that can respectively increase and stabilize process rates in ecosystems. For example, predator complementarity and redundancy can determine prey consumption rates and their stability, yet few studies take into account the multiple predator species attacking multiple prey at different rates in natural communities. Thus, it remains unclear whether these biodiversity mechanisms are important determinants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
69
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(79 citation statements)
references
References 66 publications
7
69
1
Order By: Relevance
“…In our study, the increased number of parasitoid species attacking the same host species at edges provides functional redundancy, which has been shown using the same dataset here to reduce the spatial variability of parasitoid-host interactions (Peralta et al 2014) and elsewhere to increase parasitism rates (Tylianakis et al 2006).…”
Section: Accepted Articlesupporting
confidence: 63%
“…In our study, the increased number of parasitoid species attacking the same host species at edges provides functional redundancy, which has been shown using the same dataset here to reduce the spatial variability of parasitoid-host interactions (Peralta et al 2014) and elsewhere to increase parasitism rates (Tylianakis et al 2006).…”
Section: Accepted Articlesupporting
confidence: 63%
“…Parasitoids (Hymenoptera and Diptera) were identified morphologically after their emergence. For male Hymenoptera parasitoids that could not be identified morphologically, we sequenced a region of the mitochondrial cytochrome C oxidase subunit I (COI) used in previous studies for parasitoid identification (Kaartinen, Stone, Hearn, Lohse, & Roslin, ), and related male sequences to those of female specimens that had been identified morphologically (see Peralta et al., for more details on species identification). A list of the plant, herbivore and parasitoid species involved in this study, and locations where voucher specimens have been deposited, can be found in Table S1 in Appendix ).…”
Section: Methodsmentioning
confidence: 99%
“…The pine forests at our edges were between 17 and 28 years of age, with trees mature enough that the canopies were closed. We describe the understory vegetation composition of the two forest types elsewhere2135. Each forest (plantation or native) was large enough to have an interior location at least 400 m from all edges.…”
Section: Methodsmentioning
confidence: 99%